Relationships and Supports Study: People with Intellectual Disabilities in Ireland - Garcia Iriarte, Edurne (Trinity College Dublin; National Federation of Voluntary Bodies, 2010)
We came up with the idea of doing a research project on what people think about friendships, relationships, and supports.
PUBLISHED
Dublin
Keywords: Human Rights; INTELLECTUAL DISABILITY; STAFF SUPPORT; SUPPORT; romantic relationships